Standardisation of in vitro propogation Techniques in Thathiri (woodfordia fruticosa (L.) Kurz.) - Gayathri G (Department of Plant Breeding and Genetics, College of Horticulture, 2005)
The present study ‘Standardisation of in vitro propagation techniques in thathiri [Woodfordia fruticosa (L.) Kurz.]’ was undertaken in the Department of Plant Breeding and Genetics, College of Horticulture, Vellanikkara during 2003-2005 through the conduct of two experiments viz. (i) direct regeneration and (ii) regeneration through callus mediated organogenesis.